The Influence of Service Quality, Promotions and Prepaid Prices on Customer Decisions at PT PLN (Persero) Palembang - Hafiz Hafiz; Marlina Widiyanti; Aslamia Rosa; Muchsin Saggaf (International Journal Labs, 2024)
This study aims to determine the influence of service quality, promotions and prepaid prices on customer decisions at PT PLN (Persero) Palembang. The population in this study is all customers at PT PLN (Persero), both prepaid electricity customers in 2023 in Palembang City. The sample conducted in this study was 100 respondents, namely by purposive sampling method. The results of multiple linear regression analysis show that service quality, promotion and price have a positive and significant effect on customer decisions. Service quality, it is expected that PT PLN (Persero) Palembang will always make improvements in terms of services provided. As a monopolist, PT PLN (Persero) needs to provide good service for its customers. By being responsive in the process and responding to complaints as well as criticism and suggestions given by consumers. Promotion, it is expected to do promotions with promo prices that are not only done on certain dates. In addition, when doing promotions to be informed through print and electronic media. Price, it is expected to be adjusted prices for increasing electric power.